Advances in Stellar Interferometry 2006
DOI: 10.1117/12.673388
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of spatial filtering capabilities of single mode infrared fibers

Abstract: Spatial filtering is necessary to achieve deep nulls in optical interferometer and single mode infrared fibers can serve as spatial filters. The filtering function is based on the ability of these devices to perform the mode-cleaning function: only the component of the input field that is coupled to the single bound (fundamental) mode of the device propagates to the output without substantial loss. In practical fiber devices, there are leakage channels that cause light not coupled into the fundamental mode to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The presented technique is an improvement on measurements we reported previously [6]. First, it delivers independent measurement of T F , which is important for designing the optical system and for optimizing the fiber fabrication.…”
Section: Introductionmentioning
confidence: 91%
“…The presented technique is an improvement on measurements we reported previously [6]. First, it delivers independent measurement of T F , which is important for designing the optical system and for optimizing the fiber fabrication.…”
Section: Introductionmentioning
confidence: 91%
“…The use of modal filters increases the rejection ratio (or, equivalently, relaxes requirements on the wavefront quality) by reducing the sensitivity to small wavefront errors. Ksendzov et al [31,32] reported a technique for measuring the modal filtering ability of single mode chalcogenide fibers. The ideal modal filter rejects all input field components that have no overlap with the fundamental mode of the filter and does not attenuate the fundamental mode.…”
Section: Mid-infrared Single Mode Fibers As Modal Filtersmentioning
confidence: 99%
“…(b) Planet detection using a two-beam interferometer. Configurations with and without the use of a modal filter (denoted as A and B, respectively) are shown[31,32].…”
mentioning
confidence: 99%
“…limit stellar rejection). At longer MIR wavelengths (∼10 µm), there are fewer materials available to make fibers, and fiber lengths are limited [583,584], both potentially limiting the approach to true SM rejection. SMFs are also sensitive to environmental (i.e.…”
Section: Current and Future Challengesmentioning
confidence: 99%